Development and out-scaling of ISRIZ09, an aromatic hybrid rice variety for Sub-Saharan Africa - CGIAR Research Program on Rice (2019)
Aromatic hybrid, ISRIZ09, was released in Senegal in 2017 for irrigated systems. Field days and training workshops on hybrids were organized by AfricaRice and partners in Senegal and Cote d’Ivoire in 2019. On0farm demonstrations, seed production and dissemination activities are on-going in Senegal.